A new nanomagnetic Pd-Co bimetallic alloy as catalyst in the Mizoroki–Heck and Buchwald–Hartwig amination reactions in aqueous media - Sara Sobhani (Nature Portfolio, 2021)
Abstract A Pd-Co bimetallic alloy encapsulated in melamine-based dendrimer supported on magnetic nanoparticles denoted as γ-Fe2O3@MBD/Pd-Co was synthesized by a facile co-complexation-reduction method and characterized sufficiently. The catalytic evaluation of γ-Fe2O3@MBD/Pd-Co showed promising results in the Mizoroki–Heck and Buchwald–Hartwig amination reactions of various iodo-, bromo- and challenging chloroarenes in aqueous media. The synergetic cooperative effect of both Pd and Co and dispersion of the catalyst in water due to the encapsulation of γ-Fe2O3 by melamine-based dendrimer lead to high catalytic performance compared with the monometallic counterparts. The dispersion of the magnetic catalyst also facilitates the recovery and reuse of the catalyst by ten consecutive extraction and final magnetic isolation with no loss of catalytic activity, keeping its structure unaltered.